2011
DOI: 10.1007/s00520-011-1104-1
|View full text |Cite
|
Sign up to set email alerts
|

Music’s relevance for adolescents and young adults with cancer: a constructivist research approach

Abstract: Music can signify and creatively enable AYAs' hope, endurance, identity development, and adjustment through cancer treatment and post-treatment phases. Health professionals are encouraged to support AYAs' music-based self-care and "normalized" activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 31 publications
0
46
0
Order By: Relevance
“…Using a constructivist grounded theory methodology, O’Callaghan and colleagues [31] found that interactions with music were helpful during and post-treatment for 12 AYAs to facilitate positive emotions and states, as well as transition off treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Using a constructivist grounded theory methodology, O’Callaghan and colleagues [31] found that interactions with music were helpful during and post-treatment for 12 AYAs to facilitate positive emotions and states, as well as transition off treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve of these articles focused on interventions aiming to alleviate procedural distress. 191,194,[198][199][200][201][202][203][204][205][206][207] DOI: 10.3310/hta23220 HEALTH TECHNOLOGY ASSESSMENT 2019 VOL. 23 NO.…”
Section: Study Selectionmentioning
confidence: 99%
“…164,170,172,178,183,187,189,193,200,203,206,208,211,[215][216][217][218][219] Twenty-two out of the 57 studies included only CYP participants. 114,119,162,163,[166][167][168][169]184,186,187,[194][195][196][197]204,207,210,211,213,215,219 One study collected data only from practitioners who delivered the intervention. 205 Four studies collected data from parents only; 185,201,202,206 the remaining 30 studies included a mix of participant types.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations